2022
DOI: 10.1007/s00702-022-02495-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma autoantibodies to glial fibrillary acidic protein (GFAP) react with brain areas according to Braak staging of Parkinson’s disease

Abstract: Idiopathic Parkinson’s disease (PD) is characterized by a progredient degeneration of the brain, starting at deep subcortical areas such as the dorsal motor nucleus of the glossopharyngeal and vagal nerves (DM) (stage 1), followed by the coeruleus–subcoeruleus complex; (stage 2), the substantia nigra (SN) (stage 3), the anteromedial temporal mesocortex (MC) (stage 4), high-order sensory association areas and prefrontal fields (HC) (stage 5) and finally first-order sensory association areas, premotor areas, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Growing evidence suggests a correlation between GFAP and PD pathology [ 1 , 32 34 ]. Reportedly, brain areas that are destroyed early in the development of PD have particularly high levels of GFAP [ 3 ]. An animal study found the injection of Adeno-GFAP-GFP virus into the substantia nigra pars compacta caused severe reactive astrogliosis and exacerbated the accumulation of α-synuclein [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growing evidence suggests a correlation between GFAP and PD pathology [ 1 , 32 34 ]. Reportedly, brain areas that are destroyed early in the development of PD have particularly high levels of GFAP [ 3 ]. An animal study found the injection of Adeno-GFAP-GFP virus into the substantia nigra pars compacta caused severe reactive astrogliosis and exacerbated the accumulation of α-synuclein [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited between February 2015 and November 2020 and followed for up to 5 years. The inclusion criteria included the following: [ 1 ] patients had a disease duration of less than 3 years at the time of enrollment; [ 2 ] the clinical picture as well as the brain magnetic resonance imaging (MRI) excluded vascular parkinsonism and atypical parkinsonism; [ 3 ] patients were willing to follow-up annually and were diagnosed with clinically established PD at the last follow-up according to the MDS clinical diagnostic criteria [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, astrocytes can (1) release a variety of neurotoxic chemokines and cytokines, such as IL-6 [18,41,52,53]; (2) recruit and activate microglia, causing inflammatory damage [54]; and (3) present antigens and activate T-cells [55], causing immune damage. Third, astrocytes can provide antigens for anti-GFAP autoimmunoreactivity from peripheral blood in the context of leakage of the blood-brain barrier because of α-syn deposition [56,57]. Therefore, α-syn deposition can result in astrogliosis, astrocytic dysfunction, and eventually dysosmia.…”
Section: Discussionmentioning
confidence: 99%